PSYCHOLOGICAL ASPECTS OF TEACHING SINGING TO PRESCHOOL CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the psychological dimensions of teaching preschool children to sing. Singing is one of the earliest and most natural forms of musical activity, yet it involves not only physiological and pedagogical factors but also complex psychological processes. Children’s motivation, emotional development, cognitive readiness, memory, imagination, and self-confidence all play critical roles in the effectiveness of early vocal education. The article examines the psychological challenges educators face when teaching young children to sing and suggests approaches to foster positive attitudes, reduce anxiety, and create supportive environments. The findings highlight that psychological sensitivity is as important as technical instruction in helping preschool children develop a lifelong love for singing and music.